National standards for the practice of ecological restoration in Australia (vol 24, pg S1, 2016) - McDonald, T.; Jonson, J.; Dixon, Kingsley (Blackwell Science Inc., 2016)
Tein McDonald, Justin Jonson, Kingsley W. Dixon (2016) National standards for the practice of ecological restoration in Australia. Restoration Ecology 24:S1:S4-S32.DOI: 10.1111/rec.12431In McDonald et al. 2016, Byrne et al. 2013 has been inadvertently included in the reference list. We apologize for this error.